Sentinel lymph node biopsy versus pelvic lymphadenectomy in early-stage cervical cancer: a multi-center randomized trial (PHENIX/CSEM 010). Issue 11 (November 2020) - Tu, Hua; Huang, He; Xian, Bingna; Li, Jibin; Wang, Ping; Zhao, Weidong; Chen, Xiaojun; Xie, Xing; Wang, Chunyan; Kong, Beihua; Xiao, Jing; Zhang, Ping; et al.
Abstract : Background: There is no accepted strategy for applying sentinel lymph node (SLN) biopsy as an alternative to pelvic lymphadenectomy in cervical cancer. It is unclear whether and when pelvic lymphadenectomy can be safely replaced by SLN biopsy alone. Primary Objective: To comprehensively compare the oncological outcomes of SLN biopsy with pelvic lymphadenectomy in patients with and without SLN metastasis. Study Hypothesis: It is hypothesized that the oncological outcomes provided by SLN biopsy are non-inferior to those of pelvic lymphadenectomy in patients with clinically early-stage cervical cancer if risk-adapted adjuvant treatments are given. Trial Design: All eligible patients will undergo SLN biopsy at the start of surgery. The resected SLNs will be submitted for frozen section examination. and patients will be triaged into the PHENIX-I (SLN-negative) or PHENIX-II (SLN-positive) cohort. In each cohort of this trial, patients will be randomized in a 1:1 ratio into the experimental (SLN biopsy alone) or reference (pelvic lymphadenectomy) arm. Radical hysterectomy will be performed for all patients, and adjuvant treatments will be planned according to post-operative pathological factors. Major Inclusion/Exclusion Criteria: Patients aged between 18 and 65 years with histologically confirmed, untreated stage IA1 (lymphovascular space involvement), IA2, IB1, and IB2 cervical squamous carcinoma, adenocarcinoma, or adenosquamous carcinoma. Primary Endpoint: The primary endpoint is disease-free survival. Sample Size: Estimated sample sizes of 830 and 250 are required to fulfill the study objectives of PHENIX-I and II, respectively. Estimated Dates for Completing Accrual and Presenting Results: As of May 2020, more than 600 eligible patients have been enrolled. Enrollment is expected to be completed by December 2022, and presentation of results is expected in 2026. Trial Registration: NCT02642471.